Trust-Building and Consensus Approach to Conflict Resolution: Alternative Tactics to Strike Actions in Nigeria - J. Omolekan, Olushola; Gunu, Umar (Journal of Techno-Social, 2022)
Over the years, industrial actions have been one of the crucial issues resulting to the decline in organizational productivity in Nigeria. Strike actions have been considered by the organized unions as a means of expressing their grievances and struggling for their rights and privileges. These actions have serious and negative effects on organizational efficiencies such as low productivity, loss of profit, low performance, and the eventual collapse of some promising ventures. Owing to these consequences, there is a need for alternative tactics to end this menace. Thus, the influence of trust-building and consensus approach on conflict resolution as alternative strategies to strike actions in Nigeria is examined in this study. The study adopted a survey design. A sample of selected organized labour union leaders and key top executive officers formed the respondents of the study. Cluster and simple sampling techniques were used to select sampled respondents. A validated structured questionnaire and interview were adopted to gather needed information for this study. Ordinary least square regression, correlation, and cross tabulation were used to analyze the collated data. The findings revealed that honesty, loyalty and sacrifice are significant in conflict resolution and crisis management. It was deduced from the study that conflict is unavoidable in a workplace but can be managed through a proactive measure of trust and consensus-building approach. The study recommended among others that keeping to the agreement, openness, understanding, collaborative and participative efforts are needed to enhanced organizational efficiency.